Internet como simulacro cultural malentendidos y reflexiones al respecto de las cibersociologías - Luis Anta, José (2005)
This work tries in a synthetical and maybe superficial way to connect series of theoretical and epistemological reflections about points of views related with the network that generally are found in specific literature coming from each discipline of social sciences, which seems to be oriented towards a ciberspecialization.